Toward a Holistic Legal Framework for Effective Waqf Implementation: Integrating Islamic Socio-Economic Models - Hadi, Muhammad; Rum, Jalaluddin; Maguni, Wahyudin; Radiamoda, Anwar M. (Volksgeist: Jurnal Ilmu Hukum dan Konstitusi, 2025)
Waqf is crucial in the improvement of community welfare and the resolution of socio-economic challenges.  Nevertheless, its implementation in Indonesia is beset by various legal, institutional, and managerial obstacles, such as insufficient regulations, a lack of public awareness, and inefficient governance.  This research aims to evaluate the legal framework for the effective integration of the Islamic socio-economic model into the waqf process.  This normative legal study employs a regulatory-legislative approach, conceptualization, and Lawrence M. Friedman's legal system theory to evaluate the efficacy of regulations concerning waqf.  The research's findings suggest that Indonesia's waqf regulations continue to encounter legal challenges, particularly in conjunction with the discordant regulations in settlement and the lax rules regarding productive waqf.  The effectiveness of the waqf administration is impeded by the lack of professionalism of the nazhir and the weaknesses in the supervision of the Indonesian Waqf Board (BWI) regarding legal structure.  In the meantime, the legal culture demonstrates that the community's low legal awareness results in the inadequate documentation of numerous waqf assets, rendering them susceptible to protection and underutilization.  Consequently, it is imperative to enhance the professionalism of nazhir, revise regulations, and digitize waqf management to improve transparency and efficiency.  Community participation and more stringent supervision are also necessary for optimizing waqf as an economic and social instrument.